The Effect of a Strategy Based on Some Pivotal Thinking Skills on the Achievement of Fifth-grade Literary Female Students in the Subjects of the Holy Quran and Islamic Education by Creating their High-Ranking Thinking - Sahab , Saadia (Islamic Sciences Journal, 2023)
This paper includes the experimental approach with two equal groups was chosen in the research. The research has been applied in the first semester of the academic year (2020-2021). The sample consisted of (54) female students, with (27) female students in each of the experimental and control groups. The two groups were rewarded with several variables and were prepared. The researcher sought behavioral purposes for the scientific subject, and teaching plans, and prepared two tools for research, which are an achievement test that consisted of (30) objective items and a test of pivotal thinking consisting of (42) objective and essay items. Their validity and psychometric properties have been verified, and their validity was also found.